Reasoned Action Approach Correlates of Physical Activity Among African American Men Living With HIV: A Cross-Sectional Study. (14th January 2021) - Kelly, Terri-Ann; Woko, Chioma; Jemmott, Loretta S.; Icard, Larry; Chittamuru, Deepti; Jemmott, John B.
Abstract: Physical activity (PA) is associated with a reduced incidence of chronic diseases. However, little is known about the predictors of PA among African American men living with HIV. We report secondary analyses examining the strength of the relationships between the reasoned action approach constructs, attitude, subjective norm, descriptive norm, and self-efficacy and intention to exercise and self-reported adherence to Department of Health and Human Services PA guidelines using baseline data from a trial of a PA intervention with 302 African American men, between 40 and 88 years of age ( M = 53.9; SD = 7.2) living with HIV. Multiple regression revealed that attitude, subjective norm, and self-efficacy were positively associated with intention. Logistic regression revealed higher odds of meeting PA guidelines as self-efficacy increased. Self-efficacy and descriptive norm predicted meeting the aerobic guideline. Self-efficacy predicted meeting the muscle-strengthening guideline. Interventions targeting reasoned action approach variables may contribute to efforts to improve PA among African American men living with HIV.